Sosialisasi Gangguan Stress Pada Narapidana Wanita di Lapas Perempuan Kelas IIA Palembang - Chintya Putri Dendra; Mutia Mawardah (Jurnal Pengabdian Nasional (JPN) Indonesia, 2023)
There are still many people who give people with psychological disorders bad labels such as "stress", "crazy", "defect", "strange behavior", "incurable disorder". In addition, society views people with psychological disorders as horrible, shameful, and frightening. An introduction is a medium that can be provided to a group or community with the aim of providing information on spiritual or psychological matters to increase knowledge and understanding. Referrals can not only be used for people who are experiencing psychological problems but can also be used as a social movement. The goal is to educate about mental illness. The method used is socialization which aims to increase awareness of mental health stress disorders among female prisoners. As a result, the socialization activities went smoothly according to plan. Participants or participants showed their enthusiasm in participating in the activity, shown through listening to the material, responding, discussing, and asking questions. The author hopes that with this socialization activity, participants can increase their knowledge about mental health and apply it in their daily lives. The author also hopes that the stigma attached to psychological disorders can be reduced and people who need psychological help can consult a psychologist and/or psychiatrist without shame and guilt.